2008
DOI: 10.2137/145960606780061470
|View full text |Cite
|
Sign up to set email alerts
|

Consumer evaluation of scab-resistant apple cultivars in Sweden

Abstract: The feasibility of using untrained consumers for sensory evaluation was investigated on Swedish-grown scab-resistant apple cultivars in 2002 (11 cultivars) and 2003 (15 cultivars). The consumers evaluated five cultivars each, including the control cultivar 'Aroma'. Each cultivar was scored for appearance, texture, juiciness, taste and overall impression by a minimum of 100 consumers in 2002 and by 200 in 2003. All quality attributes were positively correlated when calculations were performed across all consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…By analysing these results with the tasters, it was confirmed the taste axiom and that everyone has his/her own taste and taste cannot be wrong as it is ones' preference. Like in other studies (Jönsson and Nybom, 2008), taste and flavor, associated with optimum juiciness, were considered the most important quality traits, which can make the separation between cultivars and assure the appreciation on the market.…”
Section: No Cultivarmentioning
confidence: 82%
See 1 more Smart Citation
“…By analysing these results with the tasters, it was confirmed the taste axiom and that everyone has his/her own taste and taste cannot be wrong as it is ones' preference. Like in other studies (Jönsson and Nybom, 2008), taste and flavor, associated with optimum juiciness, were considered the most important quality traits, which can make the separation between cultivars and assure the appreciation on the market.…”
Section: No Cultivarmentioning
confidence: 82%
“…Given by specific traits, any cultivar may be (extremely) liked and disliked by consumers, with vast differences depending on the region and its specific cuisine, consumers' age and gender, education, know-how (trained tasters) etc. (Abbott et al, 2004;Jemrić et al, 2012b;Jönsson and Nybom, 2008;Seppä et al, 2013).…”
Section: No Cultivarmentioning
confidence: 99%
“…Some studies have indicated that older respondents prefer sweeter or softer fruits more than younger respondents (Harker et al . ; Jönsson and Nybom ). No such observation was made in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Genetic variation among cultivars (each cultivar usually corresponds to a single genotype in apple and other clonally propagated crops) is the basis for selection-mediated improvement, and the subsequent development of superior cultivars. Considerable variation among cultivars in their susceptibility to some of the most common storage rots has been reported from observations in orchards and storage rooms [ 3 , 19 , 21 , 40 , 43 , 70 ]. Still, levels of resistance cannot be properly quantified based only on natural infections, since the inocula may vary in both quantity and virulence.…”
Section: Quantification Of Storage Rot Damagementioning
confidence: 99%